COMPARATIVE LEXICON SYSTEM OF RUSSIAN, GERMAN, AND ENGLISH LANGUAGES (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
This article focuses on defining word-formation terminology in a comparative study of compound words in Russian, English, and German. It highlights the necessity of clarifying terms such as 'confix,' 'shift,' 'addition,' and 'fusion,' as well as finding equivalents among the types of compound words in these languages. This need arises from the unique challenges of comparative research and the diverse theoretical approaches to the study of compound words.